Exploring the Role of Aquatic Macrophytes in Phytoremediation of Heavy Metal-Contaminated Water - Stanikzai, Khalid; Chauhan, Avnish; Saadat, Mohammad Youset (Journal of Natural Sciences – Kabul University, 2026)
Some aquatic plants have a remarkable ability to absorb and accumulate heavy metals, which can be utilized in reducing water pollution. In this review, we assessed the utilization of aquatic macrophytes, specifically water hyacinth (Eichhornia crassipes), for heavy metal cleanup and sustainable wastewater treatment. After screening 12 databases, such as PubMed, Scopus, Web of Science, and ScienceDirect for the period 2019-2024, we reviewed 112 studies. Bibliometric analysis using VOS viewer (v1. 6. 18), which revealed the main research trends, citation networks and thematic clusters. The produced results suggest that (i) the water hyacinth has a high capacity of cadmium accumulation (166.25 ppm dry weight), but is very effective for the removal of lead, mercury, arsenic, and nickel. Other macrophytes, including Lemna minor, Pistia stratiotes, and Hydrilla verticillata, also have a considerable extent of chromium, copper, and zinc removed. While exposure to metals imposes physiological stress, the aquatic plants act as symptoms, causing low-cost, eco-friendly phytoremediation agents.